The Impact of Corruption on Green Growth: Theory and Empirical Evidence of Green Economy as a Source of Growth - Azwardi, Azwardi; Zainal, Rabin Ibnu; Igamo, Alghifari Mahdi (International Journal of Energy Economics and Policy, 2025)
The potential for economic growth through green growth can be driven by good governance. The purpose of this study is to further clarify the scientific concept, and proof of concept between the quality of governance in the form of controlling the level of corruption on green growth in high-income and lower-middle-income countries. The research objects are divided into 26 countries included in developed countries and 8 countries included in developing countries in Asia using panel data for the period 2019-2023. The results of the study show that controlling corruption has a significant negative impact on green growth, especially in countries with high income levels. This shows that the level of corruption control in these countries has not been effective during the observation period. Corruption hinders the implementation of effective environmental policies, weakens regulations, and causes inefficient resource allocation, especially in the energy and industrial sectors. This worsens environmental conditions and reduces green innovation which is essential for sustainable growth. However, the results of this study indicate that spending on environmental protection has a positive impact on green growth in the model of lower-middle income and high-income countries. In addition, the results of the study indicate that economic development and growth also have a negative effect on green growth, there is resource depletion due to economic activities. Thus, to achieve green growth and advance the 2030 Agenda for Sustainable Development Goals, anti-corruption policies must be implemented actively to strengthen environmental regulations and support green growth.